Pancasila Feminism: Gender Equality Based on Values of Pancasila - Cahya Wulandari; Indung Wijayanto; Loso . (Faculty of Law, Universitas Pekalongan, 2022)
AbstractFeminist are trying to fight for women in Indonesia to stand in line with men. However, these struggles are often based on liberal ideology. Gender equality based on liberal values can certainly be contrary to the values of Pancasila. Based on this, it needs to be discussed related to Pancasila Feminism as a form of gender justice based on the values of Pancasila precepts. Feminism based on human rights must still respect the differences in culture, nation and religion embraced by each country. In Pancasila feminism, all gender equality struggles must be in accordance with the nature of Pancasila which includes awareness as a creature of God, awareness as a civilized and just human being, awareness as a social being, unity and nationhood, and the ability to consult consensus. The views of feminism should not be contrary to the values of Pancasila, especially, with the value of Godhead. Religion considers that the position of men and women is equal in God's eyes. However, equality does not mean in all things for example in domestic and inheritance affairs.Keywords: Feminism, Gender Equality, Pancasila AbstrakPara pemerhati feminisme berusaha memperjuangkan kaum perempuan di Indonesia untuk berdiri sejajar dengan laki-laki. Namun, perjuangan tersebut seringkali berpedoman pada ideologi liberal. Kesetaraan gender yang berlandaskan nilai-nilai liberal tentu dapat bertentangan dengan nilai-nilai Pancasila. Berdasarkan hal tersebut, perlu dibahas terkait Feminisme Pancasila sebagai bentuk keadilan gender yang berbasis pada nilai-nilai sila Pancasila. Feminisme yang berdasar pada hak asasi manusia harus tetap menghormati perbedaan budaya, bangsa dan agama yang dianut masing-masing negara. Dalam feminisme Pancasila, semua perjuangan keseteraan gender harus sesuai dengan sifat Pancasila yang meliputi kesadaran sebagai makhluk Tuhan, kesadaran sebagai manusia yang beradab dan berkeadilan, kesadaran sebagai makhluk sosial, bersatu dan berbangsa, dan kemampuan bermusyawarah mufakat. Pandangan feminisme tidak boleh bertentangan dengan nilai-nilai Pancasila, terutama, dengan nilai Ketuhanan. Agama menganggap bahwa kedudukan laki-laki dan perempuan adalah sama di mata Tuhan. Namun, kesetaraan itu bukan berarti dalam segala hal misal dalam urusan rumah tangga dan waris. Kata Kunci: Feminisme, Kesetaraan Gender, Pancasila